MANAGEMENT ACCOUNT AS ONE OF THE DIRECTIONS IMPROVING THE DOMESTIC ACCOUNTING SYSTEM - Шурпенкова, Руслана; Сарахман, Оксана; Калайтан, Тетяна (Socio-economic relations in the digital society, 2019)
Considered the feasibility of the use of management accounting in various enterprises by volume. Highlighted the main differences of financial and management accounting. Management accounting allows you to get information about the activities of the enterprise for internal users in the process of managing the enterprise. The main functions, methods and components of management accounting are investigated, as well as the principles inherent in the management accounting are taken into account. In clause the concept of the budgeting as method of the management account is analysed, the basic principles of the budgeting are considered; the display of the budgeting in the reporting is proved. The obligatory condition of efficiency of the system of management accounting is the coherence of the work of all services and units of the enterprise, constant team cooperation in the direction of the implementation of the agreed overall goals of the enterprise. Implementation of managerial accounting at the enterprise will increase the analyticity and effi ciency of data.
Keywords: accounting; budgeting, automation; functions; ERP-systems management account; tax burden; accounting organization; reporting; responsibility centers; cost centers; place of origin for costs